Sensitive Integration of Multilevel Optimization Model in Human Activity Recognition for Smartphone and Smartwatch Applications - Samaher Al-Janabi; Ali Hamza Salman (Big Data Mining and Analytics)
This study proposes an intelligent data analysis model for finding optimal patterns in human activities on the basis of biometric features obtained from four sensors installed on smartphone and smartwatch devices. The proposed model, referred to as Scheduling Activities of smartphone and smartwatch based on Optimal Pattern Model (SA-OPM), consists of four main stages. The first stage relates to the collection of data from four sensors in real time (i.e., two smartphone sensors called accelerometer and gyroscope and two smartwatch sensors of the same name). The second stage involves the preprocessing of the data by converting them into graphs. As graphs are difficult to deal with directly, a deterministic selection algorithm is proposed as a new method to find the optimal root to split the graphs into multiple subgraphs. The third stage entails determining the number of samples related to each subgraph by using the optimization technique called the lion optimization algorithm. The final stage involves the generation of patterns from the optimal subgraph by using the association pattern algorithm called gSpan. The pattern finder based on Forward-Backward Rules (FBR) generates the optimal patterns and thus aids humans in organizing their activities. Results indicate that the proposed SA-OPM model generates robust and authentic patterns of human activities.